Psychogenic nonepileptic seizures: diagnosis and initial management. (December 2010) - Duncan, Roderick
Psychogenic nonepileptic seizures (PNES; also known as pseudoseizures, nonepileptic attack disorder) are common. They continue to pose diagnostic difficulties, with mean delays from onset to diagnosis of several years, during which time they are often treated as epilepsy. The literature suggests that clinical diagnosis has limited reliability. However, it may be useful to regard the diagnosis of PNES as having two stages – that of suspecting the diagnosis and that of confirming it. Clinical features of the history and spells allow the diagnosis of PNES to be suspected in the first place, so that the appropriate expertise and tests can be brought to bear. The diagnosis of PNES is usually confirmed by recording spells using video EEG. A minority of patients also have epilepsy. Once the diagnosis is made, initial management consists of communicating the diagnosis to the patient and carers in a clear and nonpejorative way, as well as withdrawing anticonvulsant medication with appropriate monitoring in patients with no evidence of epilepsy. In many patients, spells will cease without psychological intervention. Emergency healthcare utilization may drop sharply after explanation of the diagnosis, and this may occur even in patients whose spells continue. It is not clear to what degree these positive effects are maintained in the long term.